Identification of Spodoptera frugiperda biotypes (Lepidoptera: Noctuidae) through using mitochondrial and nuclear markers - VÉLEZ-ARANGO, ANA MARÍA; ARANGO-I., RAFAEL EDUARDO; VILLANUEVA M., DIEGO; AGUILERA-G., ELIZABETH; SALDAMANDO-B., CLARA INÉS (Revista Colombiana de Entomología, 2008)
Spodoptera frugiperda is considered a primary pest in corn crops and a secondary pest in rice, cotton, sorghum and pastures. It exhibits two biotypes (corn and rice) that are almost identical morphologically, but differ in their genetic composition and resistance to insecticides and Bacillus thuringiensis, with the corn biotype more resistant than the rice biotype. This work is the first molecular identification in Colombia of these biotypes for larvae collected from corn, rice and cotton crops in the department of Tolima by using a PCR-RFLP of the mitochondrial gene cytochrome oxidase subunit I (COI) for the identification of corn biotype, and a PCR amplifying a FR tandem region of the nuclear DNA to identify the rice biotype. The results differentiated three populations of S. frugiperda: a) corn biotype, composed of individuals that generated digestion products with the enzyme MspI of the COI gene, b) rice biotype, composed of individuals that generated amplification products higher than 500 bp with the FR marker, and finally c) a group of individuals classified as “hybrids” between these markers, product of the cross between a corn biotype female and rice biotype male and vice versa. Individuals genotyped as the corn biotype were collected exclusively from corn and cotton crops and the individuals genotyped as the rice biotype were mainly collected from rice crops and in low proportions from corn and cotton crops.